Benefits and drawbacks of the cost average plan as an alternative investment strategy in EMU countries - Evangelos Vasileiou; Elroi Hadad (Cogent Economics & Finance)
This study explores long-term investment strategies for individuals in European countries who have limited initial capital and may have no expertise in financial economics. We compare three strategies—Cost Average Plan (CAP), Bank Deposits Plan (BDP), and Buy and Hold (BnH)—by analyzing their risk and performance across six European Monetary Union (EMU) countries: France, Germany, Italy, Ireland, the Netherlands, and Spain, using data from January 2003 to December 2023. CAP is ideal for individuals aiming to build wealth gradually by investing a fixed amount monthly in an ETF that tracks an index, while BDP involves saving money in a bank account. This analysis also aligns with the European Commission’s Pan-European Personal Pension Product (PEPP) guidelines. The findings reveal that CAP generally outperforms monthly bank deposits, making it a better choice for those unable to invest large sums upfront, such as young individuals or new parents with long-term savings goals. Although CAP underperforms BnH in terms of returns, it offers significantly lower risk, making it suitable for investors with moderate risk tolerance. Additionally, CAP demonstrates greater stability in adverse market conditions compared to BnH. Future research could build on these results by incorporating more variables, markets, and investment horizons.